102k views
0 votes
2^2+(24÷4)-6=16-444.5

User Carfield
by
5.0k points

1 Answer

3 votes

Answer:

4

Step-by-step explanation:

Given the expression:


2^2+\mleft(24/4\mright)-6

We use the order of operation: PEMDAS (Parentheses, Exponent, Multiplication, Division, Addition and Subtraction).

First, we evaluate P-Parentheses.


=2^2+6-6

Next, evaluate E-Exponents:


=4+6-6

Since we are left with addition and subtraction, we simplify:


\begin{gathered} =4+0 \\ =4 \end{gathered}

The result is 4.

User Karol Samborski
by
5.8k points